A triple-amplification strategy based on the formation of peroxidase-like two-dimensional DNA/Fe3O4 networks initiated by the hybridization chain reaction for highly sensitive detection of microRNA. Issue 58 (24th June 2019) - Tang, Sheng; Li, Yana; Zhu, Anni; Yao, Yao; Sun, Jun; Zheng, Fenfen; Lin, Zixia; Shen, Wei
Abstract : Peroxidase-like two-dimensional DNA/Fe3 O4 networks were constructed by the hybridization chain reaction and applied to detect microRNA down to the aM level. Abstract : A highly sensitive triple-amplification assay for the detection of microRNA (miRNA) let-7a is reported in this work. The assay relies on the formation of magnetic two-dimensional DNA/Fe3 O4 nanosheet networks initiated by the target miRNA-associated hybridization chain reaction. The Fe3 O4 nanosheets in the DNA/Fe3 O4 networks display peroxidase-like catalytic activity towards a colorimetric reaction, thereby producing a highly sensitive signal for the quantification of let-7a . Under optimal conditions, the assay achieved a detection limit of 13 aM at a signal-to-noise ratio of 3 and a linear calibration plot between 0.05 fM and 12 nM. Successful attempts were made in the quantification of let-7a in serum samples.